A Comparative Study of Flavonoids and Carotenoids Revealed Metabolite Responses for Various Flower Colorations Between Nicotiana tabacum L. and Nicotiana rustica L. - Xiao, Qinzhi; Zhu, Yueyi; Cui, Guoxian; Zhang, Xianwen; Hu, Risheng; Deng, Zhengyu; Lei, Lei; Wu, Liwen; Mei, Lei (Frontiers in Plant Science, 2022)
Tobacco is a model plant for studying flower coloration. Flavonoids and carotenoids were reported to contribute to the flower color in many plants. We investigated the mechanism underlying flower color formation in tobacco by comparing the profiling flavonoids and carotenoids between various species Nicotiana tabacum L. and Nicotiana rustica L., as their flowers commonly presented red (pink) and yellow (orange), respectively. The metabolomes were conducted by UPLC-ESI-MS/MS system. The main findings were as follows: 1) Thirty-one flavonoids and thirty-six carotenoids were identified in all four cultivars involved in N. tabacum and N. rustica. 2) Flavonoids and carotenoids tended to concentrate in the red flowers (N. tabacum) and yellow flowers (N. rustica), separately. 3) Eight flavonoids and twelve carotenoids were primary screening out for the metabolic biomarkers, the robust biomarker involving kaempferol-3-o-rut, quercetin-glu, rutin, lutein, and β-carotene. This is the first research of systematic metabolome involving both flavonoids and carotenoids in tobacco flower coloration. The metabolic mechanism concluded that flavonoids and carotenoids mainly and separately contributed to red (pink) and yellow (orange) tobacco flowers. Our finding will provide essential insights into characterizing species and modifying flower color in tobacco breeding through genetic improvement or regulation of featured metabolic synthesis.